2001
DOI: 10.1007/s100520100787
|View full text |Cite
|
Sign up to set email alerts
|

Plasma production and thermalisation in a strong field

Abstract: Aspects of the formation and equilibration of a quark-gluon plasma are explored using a quantum kinetic equation, which involves a non-Markovian, Abelian source term for quark and antiquark production and, for the collision term, a relaxation time approximation that defines a time-dependent quasi-equilibrium temperature and collective velocity. The strong Abelian field is determined via the simultaneous solution of Maxwell's equation. A particular feature of this approach is the appearance of plasma oscillatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 25 publications
(46 reference statements)
2
54
1
Order By: Relevance
“…2 Also, in what follows, we take into account neither the collision between the created particles nor their inherent radiation fields. Previous investigations on these subjects have revealed that the effects induced by both phenomena are irrelevant for the PP whenever the field strength E is weaker than the critical one E c [43][44][45] and this is in fact the regime in which we are interested.…”
Section: Quantum Kinetic Approachmentioning
confidence: 97%
“…2 Also, in what follows, we take into account neither the collision between the created particles nor their inherent radiation fields. Previous investigations on these subjects have revealed that the effects induced by both phenomena are irrelevant for the PP whenever the field strength E is weaker than the critical one E c [43][44][45] and this is in fact the regime in which we are interested.…”
Section: Quantum Kinetic Approachmentioning
confidence: 97%
“…In Ref. [437,458,459,460,267], the quantum Vlasov equation has been numerically studied to show the plasma oscillations and the non-Markovian effects. They are also compared with the Boltzmann-Vlasov equation (534) that corresponds to the Markovian limit.…”
Section: Quantum Vlasov Equationmentioning
confidence: 99%
“…The mean values of momentum p(t) and energyǭ(t) are computed [460] by using distribution function F (p, t) regularized via the procedure described in Ref. [458] that yields the renormalized electric current (556).…”
Section: Collision Decoherence In Plasma Oscillationsmentioning
confidence: 99%
“…(178) can be justified in the mean field approximation based on the large-N f expansion [83], or by the classical-statistical approximation for strong gauge fields [77]. Numerical computations including the back reaction problem have been conducted in several studies [57,62,77,[84][85][86][87][88][89][90][91][92][93]. Figure 10: The time evolution of the electrical field E z (t) scaled by its initial value E 0 (solid line, left axis), and the induced charge current J z (t) divided by (eE 0 ) 3/2 (dotted line, right axis).…”
Section: Back Reactionmentioning
confidence: 99%